Matematik asas for higher education / Young Choon Hoong - Young , Choon Hoong (2002)
This report was based on the final year project, as a partial requirement for the degree of Computer Science. The title of this project is "Matematik Asas" For Higher Education. This report contains three chapters, which are introduction of this project, literature review and methodology. "Matematik Asas" For Higher Education is a project to create an educational package for student aged 17 and above. The primary objective of this project is to build up interesting educational software to give lesson to students especially in university on Mathematics Asas. This project will mainly focus on multimedia interface to keep attention from students in learning this subject and ways to enhance current teaching problem. With this developed package, students could have alternative ways to learn mathematics and thus improve their performance in the course.This report will describe the system that will be develop review on whatever had been found and analysis, and methodology that are using.